Historical roots of Agile Methods: Where did “Agile Thinking” come from? - Abbas, Noura; Gravell, Andrew M.; Wills, Gary B. (Springer Berlin Heidelberg, 2008)
The appearance of Agile methods has been the most noticeable change to software process thinking in the last fifteen years [16], but in fact many of the “Agile ideas” have been around since 70’s or even before. Many studies and reviews have been conducted about Agile methods which ascribe their emergence as a reaction against traditional methods. In this paper, we argue that although Agile methods are new as a whole, they have strong roots in the history of software engineering. In addition to the iterative and incremental approaches that have been in use since 1957 [21], people who criticised the traditional methods suggested alternative approaches which were actually Agile ideas such as the response to change, customer involvement, and working software over documentation. The authors of this paper believe that education about the history of Agile thinking will help to develop better understanding as well as promoting the use of Agile methods. We therefore present and discuss the reasons behind the development and introduction of Agile methods, as a reaction to traditional methods, as a result of people’s experience, and in particular focusing on reusing ideas from history.
Keywords: Agile methods; Software Development

Adaptive Management for International Development Programs - Loveridge, Donna (Australasian Evaluation Society Conference, 2007)
Capacity development, that is “the process whereby people, organisations and society as a whole unleash, strengthen, create, adapt and maintain capacity over time” (OECD 2005) has been a key aim of international aid programs. However, capacity development efforts have not met with resounding success despite approximately 25%, or USD15 billion a year, being spent by donors in recent years on technical assistance1 which has predominantly been aimed at developing capacity. A 1998 review by the World Bank (World Bank 1998) found that the success rate for capacity development efforts was between 30 – 40%. The Commission for Africa (2005) noted in 2005 that achievements were below expectations. The OECD (2007) sees capacity development as being one of the areas which are least responsive to development assistance and therefore one of the greatest challenges. This paper proposes that development practitioners and donors could benefit from taking an evaluative inquiry-type of approach to the design, implementation and monitoring and evaluation of capacity development programs. An alternative approach, “adaptive management”, is proposed. Adaptive management moves away from a rational linear A + B = C approach to capacity development towards constructing and testing theories of change2 for knowledge generation, adaptation and program improvement.

The Success Case Method: A Simple Evaluation Tool to Identify Critical Success Factors and Program Impa - Bell, Catherine; McDonalds, Diane (2006 Australian Evaluation Society International Conference, 2006)
Identification and reporting of critical success factors and program impact in an efficient, yet comprehensive manner is an inherent difficulty facing many evaluators of large-scale evaluations. This paper details how two evaluators encountered such problems in the initial review of a large-scale initiative and then successfully addressed these issues through the application of the Success Case Method in a subsequent evaluation of the same program. The Success Case Method is a down-to-earth evaluation tool that can be used for: finding out what is working and what is not, which also provides accurate and trustworthy information that can be used to make timely decisions (Brinkerhoff, 2003, p.3). This paper reports on the advantages of applying this approach to the evaluation of the Primary Welfare Officer Initiative (PWOI), a program that aims to improve the capacity of schools to support students at risk of disengagement and who are not achieving their educational potential.

Information and Communications Technology for Development (ICT4D)-A design challenge? - Tongia, Rahul; Subrahmanian, Eswaran (IEEE, 2006)
Keywords: IMPORTANT